Measure Theory and Integration - Barra, G. De (New Delhi: New Age, 2013)
This text approaches integration via measure theory as opposed to measure theory via integration, an approach which makes it easier to grasp the subject. Apart from its central importance to pure mathematics, the material is also relevant to applied mathematics and probability, with proof of the mathematics set out clearly and in considerable detail. Numerous worked examples necessary for teaching and learning at undergraduate level constitute a strong feature of the book, and after studying statements of results of the theorems, students should be able to attempt the 300 problem exercises which test comprehension and for which detailed solutions are provided.
References 229p.; Index 231-234p.; Reprint 2015
Keywords: Convergence; Jordan decomposition; Lebesgue-stieltjes; Abstract measure spaces